HEAR US: a qualitative study of racial discrimination in Boston’s Chinatown and empowering change from within the community - Chen, Siyu; Luo, Yajing; Dong, Kimberly R.; Yau, Yoyo; Hires, Ben; Liang, Shiwei; Tang, Alice M. (Frontiers in Public Health, 2023)
Objective To qualitatively explore the impact of anti-Asian racism in a Chinese community in the greater Boston area. Methods Individual semi-structured interviews (n = 27) were conducted between June and September 2021. Eligible participants were ethnic Chinese immigrants living in the Boston area, who were recruited through a community-based organization and by word-of-mouth. Interviews were conducted in Mandarin and Cantonese and translated into English. Data were coded and analyzed using a directed approach to content analysis. Results The majority of participants reported personal experiences of anti-Asian racism, ranging from microaggressions to violent attacks. Although lockdown and isolation during COVID-19 affected all communities, the Chinese community suffered unique and prolonged trauma stemming from the fear of violent attacks against Asians. The older person/people, in particular, were severely isolated due to fear of exposure to anti-Asian hate crimes. Participants reported a variety of emotional, mental, and physical health effects associated with feelings of fear, anxiety, isolation, and powerlessness. Many preferred to engage in self-protective behavior changes rather than relying on external resources. Conclusion Participants advocated for more education, community, and governmental support, and increased allyship between communities of color. These findings provide cultural context on the trauma this population faces and can inform further actions to address the wide range of reported health effects.